Phylogenetic diversity analysis reveals Bradyrhizobium yuanmingense and Ensifer aridi as major symbionts of mung bean (Vigna radiata L.) in Pakistan - Hakim, Sughra (Braz J Microbiol, 2020)
The present study was carried out to evaluate the diversity of rhizobia associated with nodules of mung bean in Pakistan, because this information is necessary for inoculum development. Based on sequence analysis of 16S rRNA gene of thirty-one bacteria, 11 were assigned to genus Bradyrhizobium, 17 to Ensifer, and 3 to Rhizobium. Phylogenetic analyses on the basis of 16S-23S ITS region, atpD, recA, nifH, and nodA of representative strains revealed that B. yuanmingense is the predominant species distributed throughout different mung bean–growing areas. Among the fast-growing rhizobia, Ensifer aridi was predominant in Faisalabad, Layyah, and Rawalpindi, while E. meliloti in Thal desert. Sequence variations and phylogeny of nifH and nodA genes suggested that these genes might have been co-evolved with the housekeeping genes and maintained by vertical gene transfer in rhizobia detected in the present study. Host infectivity assay revealed the successful nodulation of host by rhizobia related to genera Bradyrhizobium, Ensifer and Rhizobium. Among all, Bradyrhizobium and Ensifer spp. inoculation exhibited a significantly higher number of nodules (11–34 nodules plant(−1)) and nitrogenase activity (nodule ARA 60–110 μmol g(−1) h(−1)). Contrary to the previous studies, our data reveal that B. yuanmingense and E. aridi are predominant species forming effective nodules in mung bean in Pakistan. Furthermore, to the best of our knowledge, this is the first report showing the effective symbiosis of E. aridi, E. meliloti, and Rhizobium pusense with mung bean. The diversity of rhizobia in different habitats revealed in the present study will contribute towards designing site-specific inocula for mung bean. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s42770-020-00397-9.